ANALISIS FAKTOR YANG MEMOTIVASI MAHASISWA BERWIRAUSAHA (Studi pada Mahasiswa STIE YPPI Rembang) - Dian Ayu Liana Dewi; M. Zakky Wahyuddin Azizi (BBM (Buletin Bisnis & Manajemen), 2018)
The purpose of this study was to determine what factors influence entrepreneurial motivation in 2014 STIE YPPI Rembang students. These factors include: self-efficacy that increases student motivation to gain success with entrepreneurship, risk tolerance, desire to feel freedom in work, and the influence of the entrepreneurial environment.This research uses quantitative descriptive method. The population of this study is the total 2014 STIE YPPI Rembang students, both from the Management study program and from the Accounting study program. Samples taken were 100 students of Management and Accounting study programs. Data collection uses questionnaires, interviews and documentation. Questionnaire with only 66 questionnaires. The sample technique used in this study was proportionate stratified random sampling. Test data analysis using validity, reliability, multiple linear regression tests.The results of this study indicate that all the independent variables, both the variables of self-efficacy in entrepreneurship, tolerance of risk, and the desire to feel freedom in work have a positive and significant influence on the desire and motivation of students for entrepreneurship.